THE INFLUENCE OF ACADEMIC CULTURE, TASK COMMITMENT AND THE QUALITY OF ACADEMIC SERVICES TOWARD LECTURERS’ INNOVATIVENESS IN STIE SANTA URSULA JAKARTA - KOSASIH, AHMAD (PPs UNJ, 2016)
The purpose of this research is to know the influence of academic culture, task commitment and the quality of academic services toward lecturers’ innovativeness in STIE Santa Ursula Jakarta. This research done by using quantitative survey methods.The data collecting is held using questionnaire and analyzed with path analysis.The population taken are 52 lecturers of STIE Santa Ursula. The results of this study show many academic culture positively gives direct influences to lecturers’ innovativeness, task commitment, and the quality of academic services. Based on the findings, it is obvious that some efforts are needed to increase lecturers’ innovativeness. It can be done by providing trainings to improve lecturers’ competencies and to master usages of various learning medias. Besides, those efforts will be able to enhance sustainable multi media facility procurements, in order to encourage lecturers to be innovative and to carry out scientific research.